Prototype Penuangan Air Minum Otomatis pada Dispenser - Hoseir, Firdaus Latan; Apriando, Rama (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2025)
Automation technology has become a characteristic of every modern item, because with this automation technology it will facilitate human activities and become a benchmark or standard for modern tools including the process of pouring drinking water. So far when we want to use a dispenser, we have to wait for the water to fill up first and then turn off the tap lever manually. This causes time inefficiency and cannot be monitored for water usage which could cause the dispenser heater to burn out. With several features provided on this automatic water pouring device, users can calmly fill drinking water. The method used is the prototype method, this method is linear with the IoT project and supports the smooth process of making features such as a glass type detection sensor with 6 ultrasonic sensors (HC-SR04), servo motor rotation integrated with sensors, LCD Ic2, active buzzer, and website as a visualization of dispenser monitoring which is the result to be achieved. In conclusion, this tool has succeeded in solving the problem with several features offered